Peningkatan Produktivitas di Era Pandemi Covid 19 dengan Pengolahan Sampah Menjadi Eco Enzyme (Universitas Hasyim Asy'ari Tebuireng Jombang, 2022)
Organic waste processing can be a community empowerment program, especially for housewives. This program aims to provide insight to housewives that waste can also be processed into something more useful and of high economic value. The purpose of this program is to increase the productivity of housewives in RW 05, Kembangarum Village, Mranggen District, Demak Regency. The implementation of organic waste processing activities into eco enzyme is going very well. The organic waste used in this processing is vegetable waste, fruit peel waste and rotting fruit. The methods used in this service are presentations or lectures and demonstrations.